Effective motor learning and coordination abilities of girls and boys aged 9-10 - Matczak, Dawid; Wieczorek, Marta (Journal of Education, Health and Sport, 2023)
Introduction Learning is a complex and multi-dimensional process that depends on cognitive and emotional processes and the development of functional systems of the human body. One type of learning is motor learning. Its course and effects depend on many factors. One of the factors may be coordination abilities. Purpose The cognitive aim of the study is to assessment of the effectiveness (speed, efficiency) of learning complex motor activity in relation to the selected aspect of physical development (coordination abilities) of a selected group of girls and boys. Materials and methods The study was conducted among 73 children (44 boys and 29 girls) aged 9 - 10 years. Authors used the pedagogical experiment method and the research tool was the program for learning how to juggle three tennis balls. To assess the selected aspects of physical development we chose the direct categorized observation method. As research tools Authors used the Vienna Test System (VTS) and 2hand test. Results Boys achieved a higher average level of eye-hand coordination (2-hand test), but the differences between them and girls were not statistically significant. Girls achieved, on average, higher results than boys in terms of precise hand movements (MLS test). Statistically significant differences in their favor occurred in most of the tests performed. Conclusion There are functions between the speed and efficiency of learning a complex motor activity and coordination abilities. They are more pronounced than boys. It is important to develop coordination abilities in the didactic process to support motor learning.